Raw Material Supplier Selection Information System Using Promethee Method on Batik Tulis Lasem - A. Aviv Mahmudi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The need for raw materials for the production of Batik Tulis Lasem, apart from the Batik Tulis cooperative, is also obtained through suppliers. Selection of raw material suppliers is one of the solutions to meet the needs of raw materials, thus supporting the performance and production process. The selection of raw material suppliers must also take into account the long term, PROMETHEE is an outranking method for a limited set of alternative actions to be ranked and chosen among criteria, which are often conflicting. The development of Information Systems to support decisions on determining suppliers of raw materials for written batik SMEs is the right solution to solve problems experienced by business actors.